The liturgy of creation: understanding calendars in Old Testament context - LeFebvre, Michael (InterVarsity Press, 2019)
How were holidays chosen and taught in biblical Israel, and what did they have to do with the creation narrative? Michael LeFebvre considers the calendars of the Pentateuch, arguing that dates were added to Old Testament narratives not as journalistic details but to teach sacred rhythms of labor and worship. LeFebvre then applies this insight to the creation week, finding that the days of creation also serve a liturgical purpose.